Inhibition of fucosylation in human invasive ductal carcinoma reduces E‐selectin ligand expression, cell proliferation, and ERK1/2 and p38 MAPK activation. Issue 5 (30th March 2018) - Carrascal, Mylène A.; Silva, Mariana; Ramalho, José S.; Pen, Cláudia; Martins, Manuela; Pascoal, Carlota; Amaral, Constança; Serrano, Isabel; Oliveira, Maria José; Sackstein, Robert; Videira, Paula A.
Abstract : Breast cancer tissue overexpresses fucosylated glycans, such as sialyl‐Lewis X/A (sLe X /A ), and α‐1, 3/4‐fucosyltransferases (FUTs) in relation to increased disease progression and metastasis. These glycans in tumor circulating cells mediate binding to vascular E‐selectin, initiating tumor extravasation. However, their role in breast carcinogenesis is still unknown. Here, we aimed to define the contribution of the fucosylated structures, including sLe X /A, to cell adhesion, cell signaling, and cell proliferation in invasive ductal carcinomas (IDC), the most frequent type of breast cancer. We first analyzed expression of E‐selectin ligands in IDC tissue and established primary cell cultures from the tissue. We observed strong reactivity with E‐selectin and anti‐sLe X /A antibodies in both IDC tissue and cell lines, and expression of α‐1, 3/4 FUTs FUT4, FUT5, FUT6, FUT10, and FUT11. To further assess the role of fucosylation in IDC biology, we immortalized a primary IDC cell line with human telomerase reverse transcriptase to create the 'CF1_T cell line'. Treatment with 2‐fluorofucose (2‐FF), a fucosylation inhibitor, completely abrogated its sLe X /A expression and dramatically reduced adherence of CF1_T cells to E‐selectin under hemodynamic flow conditions. In addition, 2‐FF‐treated CF1_T cells showed a reduced migratory ability, as well as decreased cell proliferation rate. Notably, 2‐FF treatment lowered the growth factor expression of CF1_T cells, prominently for FGF2, vascular endothelial growth factor, and transforming growth factor beta, and negatively affected activation of signal‐regulating protein kinases 1 and 2 and p38 mitogen‐activated protein kinase signaling pathways. These data indicate that fucosylation licenses several malignant features of IDC, such as cell adhesion, migration, proliferation, and growth factor expression, contributing to tumor progression. Abstract : Breast invasive ductal carcinoma (IDC) overexpresses fucosylated glycans, such as sialyl‐Lewis X/A, which can be inhibited by 2‐fluorofucose (2‐FF). 2‐FF abrogates the capacity of IDC cells to bind to E‐selectin, reduces cell proliferation and cell migration, the expression of growth factor, and the activation of signal‐regulating protein kinases 1 and 2 ERK1/2 and p38 mitogen‐activated protein kinase signaling pathways. These data indicate that fucosylation inhibition prevents several malignant features of IDC.